2020
DOI: 10.1016/j.foodchem.2020.126365
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the extremely high elasticity of bulk emulsions, stabilized by Yucca Schidigera saponins

Abstract: We found experimentally that the elasticity of sunflower oil-in-water emulsions (SFO-in-W) stabilized by Yucca Schidigera Roezl saponin extract, is by > 50 times higher as compared to the elasticity of common emulsions. We revealed that strong specific interactions between the phytosterols from the non-purified oil and the saponins from the Yucca extract lead to the formation of nanostructured adsorption layers which are responsible for the very high elasticity of the oil-water interface and of the respective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…The top-down view of a large-area continuous film was observed implying spontaneous self-assembly of QS on the oil–water interface, as confirmed by scanning electron microscopy (see Figure S1 in the Supporting Information). The interface morphologies of the films for Yucca Schidigera saponins and graphene self-assembly were also found to be identical with the same pattern of wrinkles. , It can be speculated that the oil–water interfaces play a key role in the observed changes in the system.…”
Section: Experimental Results and Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The top-down view of a large-area continuous film was observed implying spontaneous self-assembly of QS on the oil–water interface, as confirmed by scanning electron microscopy (see Figure S1 in the Supporting Information). The interface morphologies of the films for Yucca Schidigera saponins and graphene self-assembly were also found to be identical with the same pattern of wrinkles. , It can be speculated that the oil–water interfaces play a key role in the observed changes in the system.…”
Section: Experimental Results and Discussionmentioning
confidence: 71%
“…As a triterpenoid bidesmosidic saponin, the sugar chain of QS is normally attached at C-3 and C-28 of the aglycone . In the molecular framework, the amphiphilic structures would adsorb at the interface to produce an overall free-energy reduction and form viscoelastic films, determining their rich physicochemical properties and biological activities. , Golemanov and co-workers have indicated the ability of QS to form stable emulsions by localizing at the oil–water interface against droplet coalescence. ,, There is an ordered rearrangement of molecules at phase boundaries to form structured domains, surface nano-wrinkles, and solid adsorption shells around oil-droplets. , Generally, the interactions between the adsorption molecules are enhanced at an oil–water planar interface resulting in extra-high elasticity, for example, H-bonds, π–π stacking, intermediate dipole–dipole attraction, and Waals attractive interactions. , Motivated by some reports, QS was used as a high-performance emulsifier in functional and engineered colloids from nanoscopic to microscopic scales ( e.g. , nanoemulsion, multicompartment emulsion, and oleogel).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently synergetic effects between interfacial elasticity and strong attractive forces among emulsion droplets was reported to lead to high bulk elastic moduli. 26 Such strong attractions among gas bubbles may also contribute to the high elastic modulus and yield stress values as well as their strong dependence on gas volume fraction observed here.…”
Section: Resultsmentioning
confidence: 64%
“…Some of the most representative succulent plants in Mexican flora are those belonging to the Yucca genus (Asparagaceae) (Matuda and Piña, 1980), with around 49 species across the Mexican territory (Rocha et al, 2006). Some species of the Yucca genus represents a source of building material (Soltani et al, 2020), food additives (Suzuki et al, 2020;Thomas-Popo et al, 2019;Tsibranska et al, 2020), and cosmetics , as well as compounds with therapeutic potential (Patel, 2012). In this regard, it has been shown that Yucca shidigera contains yuccaol A, B and C, resveratrol, and other phenolic compounds with reported biological activities (Oleszek et al, 2001) such as anti-inflammatory (Marzocco et al, 2004).…”
Section: Introductionmentioning
confidence: 99%